Copper Doped PPy/MWCNT Nanocomposite Materials for Supercapacitor Applications - Priyadarsini, M. H.; Adhikary, M. C.; Jena, P.; Pujahari, R. M. (Journal of Scientific Research, 2023)
We report the structural, morphological, and electrochemical properties of polypyrrole (PPy), copper doped PPy (Cu/PPy), and copper doped polypyrrole multi-walled carbon nanotubes (Cu/PPy/MWCTs) prepared by oxidative polymerization technique. The incorporation of Cu in the form of nanoparticles in the composites was confirmed from XRD data. The granular morphology of PPy was observed from the FESEM micrograph. However, the size of the grains was decreased with Cu nanoparticle insertion in the matrix. The uniform distribution of Cu nanoparticles in the Cu/PPy and Cu/PPy/MWCTs nanocomposites has been evidenced from TEM images. The highest specific capacitance of 311 F/g at a scan rate of 10 mV/s is achieved in the case of Cu/PPy/MWCTs composite. It is found that the cyclic stability of these nanocomposites is enhanced due to the integration of MWCNTS and Cu nanoparticles with PPy polymer. The Cu/PPy/MWCNTs nanocomposites retained 91% of their specific capacitance even after 1000 cycles. The maximum energy density of 19.89 Wh/kg and maximum power density of 4479.71 W/kg at the scan rate of 200 mV/s were also measured for the Cu/PPy/MWCNTs nanocomposite. Our study thus indicates that the prepared Cu/PPy/MWCTs nanocomposite could be a potential candidate for application in supercapacitor and hybrid type storing devices.